Answer:
6(x-4y) = 6x - 24y
Step-by-step explanation:
Here, we want to expand the given expression
We can do this using the distributive approach
We have this as;
(6 * x) - (6 * 4y)
= 6x - 24y
Answer:
20
Step-by-step explanation:
20-6=20
Answer:
174
Step-by-step explanation:
(5*3*2)+(9*3*2)+(5*9*2)
check the picture below.
now, if we split that triangle like so with that red line, we can use the right-triangle there, to get θ.
![\bf tan(\theta )=\cfrac{\stackrel{opposite}{3}}{\stackrel{adjacent}{3}}\implies tan(\theta )=1\implies tan^{-1}(\theta )=tan^{-1}(1)\implies \measuredangle \theta =\cfrac{\pi }{4}](https://tex.z-dn.net/?f=%5Cbf%20tan%28%5Ctheta%20%29%3D%5Ccfrac%7B%5Cstackrel%7Bopposite%7D%7B3%7D%7D%7B%5Cstackrel%7Badjacent%7D%7B3%7D%7D%5Cimplies%20tan%28%5Ctheta%20%29%3D1%5Cimplies%20tan%5E%7B-1%7D%28%5Ctheta%20%29%3Dtan%5E%7B-1%7D%281%29%5Cimplies%20%5Cmeasuredangle%20%5Ctheta%20%3D%5Ccfrac%7B%5Cpi%20%7D%7B4%7D)
Answer:
Step-by-step explanation:
I don’t know